Tissue‐engineered constructs: the effect of scaffold architecture in osteochondral repair. (21st March 2012) - Emans, P. J.; Jansen, E. J. P.; van, D.; Welting, T. J. M.; Woodfield, T. B. F.; Bulstra, S. K.; Riesle, J.; van, L. W.; Kuijer, R.
Abstract Cartilage has a poor regenerative capacity. Tissue‐engineering approaches using porous scaffolds seeded with chondrocytes may improve cartilage repair. The aim of this study was to examine the effect of pore size and pore interconnectivity on cartilage repair in osteochondral defects treated with different scaffolds seeded with allogenic chondrocytes. Scaffolds consisting of 55 wt% poly(ethylene oxide terephthalate) and 45 wt% poly(butylene terephthalate) (PEOT/PBT) with different pore sizes and interconnectivities were made, using a compression moulding (CM) and a three‐dimensional fibre (3DF) deposition technique. In these scaffolds, allogenic chondrocytes were seeded, cultured for 3 weeks and implanted in osteochondral defects of skeletally mature rabbits. At 3 weeks no difference in cartilage repair between an empty osteochondral defect, CM or 3DF scaffolds was found. Three months post‐implantation, cartilage repair was significantly improved after implantation of a 3DF scaffold compared to a CM scaffold. Although not significant, Mankin scores for osteoarthritis (OA) indicated less OA in the 3DF scaffold group compared to empty defects and CM‐treated defects. It is concluded that scaffold pore size and pore interconnectivity influences osteochondral repair and a decreased pore interconnectivity seems to impair osteochondral repair. Copyright © 2012 John Wiley & Sons, Ltd.